PENDAMPINGAN DAN PELATIHAN PROGRAM LDK (LATIHAN DASAR KEPEMIMPINAN) PENGURUS ORGANISASI PELAJAR PONPES AL-ISHLAH (OPPI) SENDANGAGUNG PACIRAN LAMONGAN - Rofi'i, Muhammad Arwani; Amelia, Siti Aisyah (STAI Ma'had Aly Al-Hikam Malang, 2023)
Abstract Accompanying and providing leadership training as a teaching activity to the students who are members of the OPPI Al Ishlah Islamic Boarding School board, to shape and strengthen character, foster discipline, appearance, actions and actions so that they are more courageous in making decisions. Be more confident and show empathy towards others. Starting with an initial observation stage which included interviews with trainers and school teachers who supervise OPPI administrators, as well as representatives of OPPI administrators. As there is a transition from senior management members to junior members of OPPI, mentoring and basic leadership training is necessary. This service program was carried out to accompany and train the administrators of the OPPI Al Ishlah Islamic Boarding School Sendangaggung Paciran Lamongan. Keywords: Basic leadership training, Student Organization, Al-Ishlah Islamic Boarding School. Abstrak Mendampingi dan memberikan pelatihan kepemimpinan sebagai kegiatan pengajaran kepada santri-santri yang tergabung dalam pengurus Pondok Pesantren OPPI Al-Ishlah dimaksudkan untuk membentuk dan memantapkan budi pekerti, menumbuhkan kedisiplinan, penampilan, sikap dan tindakan agar lebih berani dalam mengambil keputusan, lebih percaya diri dan menunjukkan empati terhadap orang lain. Diawali dengan tahap observasi awal yang meliputi wawancara dengan pelatih dan guru sekolah yang membawahi pengurus OPPI, serta perwakilan pengurus OPPI. Karena terdapat transisi dari anggota senior ke anggota junior OPPI, pendampingan dan pelatihan kepemimpinan dasar diperlukan. Program pengabdian ini dilaksanakan untuk mendampingi dan melatih para pengurus Pondok Pesantren OPPI Al-Ishlah Sendangaggung Paciran Lamongan. Kata Kunci: Pelatihan dasar kepemimpinan, Organisasi Kemahasiswaan, Pondok Pesantren Al-Ishlah